Group Consumption, Free Riding, and Informal Reciprocity Agreements - Thomas E. Borcherding; Darren Filson (Claremont McKenna College, Department of Economics, 2000)
We examine conditions under which group consumption is likely to involve informal and tacit reciprocity agreements rather than formal contracts and the price system. Our model shows that informal reciprocity agreements are more likely to be used when transaction costs of formal agreements are high, the good is relatively inexpensive, each consumer's demand is not too responsive to price changes, the group is likely to continue to interact over time, the consumers are patient, the time between interactions is short, and the group is small and homogeneous. Further, the results suggest that informal sharing agreements are more likely to involve goods that are consumed along with other group benefits, such as conversation and companionship. We conclude by analyzing investments in social capital and discussing the effects of deeper social interactions constrained by norm structures on our results.
Keywords: Z13; 330; club; institution; non-market; reciprocal; social capital